Performance of West Bangka Regency General Hospital - Mr Erwin (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
The purpose of this study is to know the work motivation, work environment, job stress on the performance of the hospital by using a quantitative approach. The object of this study were employees at the General Hospital of West Bangka with a total of 74 people. Data collection methods used in this study are questionnaires and interviews. Technique used in this research to get conclusion is doubled linear regression. Data analysis using multiple linear regression technique showed that Y = 0,037X1 + 0,192X2 + 0,004X3 + 2,297. This explains that the work motivation, work environment and work stress have a positive effect on employee performance.